Molecular cytogenetics for acute megakaryocytic leukemia diagnosis - E. A. Matveeva; A. N. Kazakova; I. I. Kalinina; M. E. Dubrovina; L. V. Baydun; M. A. Maschan; Yu. V. Olshanskaya; A. A. Maschan (Онкогематология)
Acute megakaryocytic leukemia (AML M7) – a rare disease characterized by poor treatment response, except for t(1;22) variant in infants. Cytogenetic abnormalities in AML M7 are highly heterogeneous. We collected samples from children with AML M7 to analyze the disease cytogenetic profile. During September 2009 to March 2012 20 AML M7 patients was studied using fluorescence in situ hybridization. Complex and heterogeneous chromosomal abnormalities were revealed. It was found that no recurring abnormalities and cytogenetic markers unique to each patients. Also, the 19p13 amplification described previously only in myeloid cell lines was detected.